Why Grow More Food?: An Analysis of Some Contradictions in the Green Revolution inKerala - Joan P. Mencher (Economic and Political Weekly, Vol. 13, No. 51/52 (Dec. 23-30, 1978), 1978)
In theory, there are a number of reasons why Third World countries are concerned about increas- ing food production, including: (1) feeding the hungry, the rural landless poor (as well as the small land- holders) and the urban poor; (2) enabling the owmers of land (be they small self-cultivating farmzers, or large producers for the market, or in between) to make a profitable living; and (3) other reasons relating to the state, to trade, and to the saving of foreign exchange. This paper, which explores data from two rice-Producing regions of Kerala, attempts to show how the first two goals of larger food production are essentially incompatible under the present social rela- tions of production